Implementasi Kebijakan Sertifikasi Halal dan Implikasinya terhadap Keberlangsungan Usaha pada Restoran dan Cafe di Kota Singkawang - Widianti, Anyta; Kurniati, Kurniati; Mustafa, Zulhas’ari (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2025)
Restaurants and cafes are one of the economic driving sectors in Singkawang City that supports the title of a tourist city. However, reality shows that there are still many practices of using halal labels without official legality by restaurant and café business actors. This study aims to understand the implementation of halal certification policies for restaurant and café business actors in Singkawang City, West Kalimantan, in the context of the implementation of halal certification obligations effective from October 18, 2024. This research is a field research using a descriptive qualitative approach. The results of the study show that the local government through the Ministry of Religion of Singkawang City has conducted socialization, mentoring, and education to restaurant and café business actors to obtain halal certification. However, challenges are still faced, such as the lack of understanding of business actors about the importance of halal certification and the practice of using halal labels without official certification. The complexity of procedures and the limitations of BPJPH human resources who do not have personnel in the regions are obstacles in itself, especially to be able to reach business actors as a whole in providing socialization and education about the importance of Halal Assurance. This study also reveals that halal certification has a positive impact on business sustainability, especially in increasing consumer loyalty and trust, increasing positive image, better business management system, and increasing business credibility.